Extracting places from traces of locations. - Hee Kang, Jong (Mobile computing and communications review.)
Location-aware systems are proliferating on a variety of platforms from laptops to cell phones. Though these systems offer two principal representations in which to work with location (coordinates and landmarks) they do not offer a means for working with the user-level notion of "place". A place is a locale that is important to a user and which carries a particular semantic meaning such as "my place of work", "the place we live", or "My favorite lunch spot". Mobile devices can make more intelligent decisions about how to behave when they are equipped with this higher-level information. For example, a cell phone can switch to a silent mode when its owner enters a place where a ringer is inappropriate (e.g., a movie theater, a lecture hall, a place for personal reflection.) In this paper, we describe an algorithm for extracting significant places from a trace of coordinates. Furthermore, we experimentally evaluate the algorithm with real, long-term data collected from three participants using a Place Lab client [15], a software client that computes location coordinates by listening for RF-emissions from known radio beacons in the environment (e.g. 802.11 access points, GSM cell towers).